Pluralism of Islamic Law in Aceh: Qanun Jinayat in the Framework of the Indonesian New Criminal Code - Mukhlis; Kamarusdiana Kamarusdiana; Utang Rosidin; Muhammad Iqbal; Nur Hidayahtul Nabihah Manas (Universitas Islam Negeri Jakarta, 2026)
This study analyzes normative conflicts between Aceh's Qanun Jinayat and the new Criminal Code through a legal pluralism framework. The focus centers on significant differences in criminal act formulations, juridical elements, and sanctions—particularly for khamr, adultery, and khalwat violations. Using a qualitative case study approach, this research draws on analysis of relevant legislation and in-depth interviews with Sharia Court judges and jinayat law practitioners in Aceh. The study reveals that legal pluralism in Aceh is dynamic, reflecting political tensions between central and regional authorities. Qanun Jinayat, rooted in fiqh al-jināyāt, now faces normative opposition from Article 613 of the new Criminal Code — a condition that requires systematic legal harmonization while risking the erosion of Aceh's long-held special autonomy. As an original contribution, this study proposes a